An unexpected phase-transformation of cobalt-vanadium layered double hydroxides toward high energy density hybrid supercapacitor - Lee, Su Chan; Kim, Mingony; Park, Jae-Ho; Kim, Eun Seong; Liu, Shude; Chung, Kyung Yoon; Jun, Seong Chan (ELSEVIER, 2021)
Vanadium-based active materials have attracted attention due to their superior characteristics such as multivalent oxidation state and low cost. Here, we report a cobalt-vanadium layered double hydroxide that can be used in a high energy density hybrid supercapacitor electrode. The molar ratio of the cobalt and vanadium is controlled to enhance the charge storage performance of the proposed cathode material. The cobalt-vanadium layered double hydroxide exhibits a high specific capacitance of 1579 F g(-1) at 1 A g(-1) current density. We determine that this high performance is attributed to an unexpected phase transform occurring in the layered double hydroxide, which is not observed in mono metal hydroxides, during the electrochemical charging process using soft X-ray-based advanced analysis. An aqueous hybrid supercapacitor based on our cathode material shows a maximum energy density of 75.71 Wh kg(-1) at a power density of 1043.72 W kg(-1) with superior cycle stability (82% after 10000 cycles).
Keywords: LITHIUM ION BATTERY; ELECTRODE MATERIALS; DOPED GRAPHENE; CARBON CLOTH; PERFORMANCE; OXIDATION; NEXAFS; METAL; OXIDE; FOAM